2021
DOI: 10.1038/s41467-021-20892-3
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell transcriptomic reveals molecular diversity and developmental heterogeneity of human stem cell-derived oligodendrocyte lineage cells

Abstract: Injury and loss of oligodendrocytes can cause demyelinating diseases such as multiple sclerosis. To improve our understanding of human oligodendrocyte development, which could facilitate development of remyelination-based treatment strategies, here we describe time-course single-cell-transcriptomic analysis of developing human stem cell-derived oligodendrocyte-lineage-cells (hOLLCs). The study includes hOLLCs derived from both genome engineered embryonic stem cell (ESC) reporter cells containing an Identificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(81 citation statements)
references
References 78 publications
(143 reference statements)
11
67
0
Order By: Relevance
“…Live imaging of OL brain organoids derived from the SOX10 reporter iPSCs subjected to our differentiation protocol revealed that SOX10 expression can be detected as early as day 7, as indicated by the presence of cells expressing photo-convertible mMaple ( Figure 1B, RFP + UV in red, white arrows). Interestingly, we found <1% of SOX10+ cells expressed KI67 at days 7 and 14 which significantly dropped to <0.5% at days 42 and 56 ( Figure 1F), consistent with recent single-cell transcriptomic analyses of human OL that revealed a cluster of OPCs are in s-phase and enriched for genes associated with cell cycle and division (Chamling et al, 2021).…”
Section: Generation Of Human Brain Organoids With Oligodendrocyte Andsupporting
confidence: 91%
See 1 more Smart Citation
“…Live imaging of OL brain organoids derived from the SOX10 reporter iPSCs subjected to our differentiation protocol revealed that SOX10 expression can be detected as early as day 7, as indicated by the presence of cells expressing photo-convertible mMaple ( Figure 1B, RFP + UV in red, white arrows). Interestingly, we found <1% of SOX10+ cells expressed KI67 at days 7 and 14 which significantly dropped to <0.5% at days 42 and 56 ( Figure 1F), consistent with recent single-cell transcriptomic analyses of human OL that revealed a cluster of OPCs are in s-phase and enriched for genes associated with cell cycle and division (Chamling et al, 2021).…”
Section: Generation Of Human Brain Organoids With Oligodendrocyte Andsupporting
confidence: 91%
“…Multiple single-cell transcriptomic studies of human OL revealed that not all oligodendroglial cells express SOX10 (Chamling et al, 2021), and that other neural cells can act as an additional source of human cortical OPCs (Huang et al, 2020), in agreement with the observation that not all OL generated in our OL brain organoids express SOX10 ( Figure 2C). To further examine this possibility, we quantified the expression of several genes that are expressed in SOX10 negative OPCs progeny as well as genes expressed in the SOX10 positive OPCs population, as identified by Chamling et al (2021). Interestingly, our qPCR analysis revealed that RTN1, ELAVL4, and HS3ST1, genes expressed in the SOX10 negative OPCs population, commenced at day 14 and persisted throughout subsequent maturation steps, whereas CRABP1 and CENPJ were only expressed at day 14 and subsequently downregulated when mature OL are specified (Figure 2E).…”
Section: Progressive Maturation Of Oligodendrocytes In Ol Brain Organsupporting
confidence: 88%
“…We used the graph-based Leiden algorithm to cluster cells and Uniform Manifold Approximation and Projection (UMAP) to visualize and annotate clusters based on expression of known marker genes, separating neurons, endothelia, and different classes of glial cells (Fig. 2B) (Chamling et al, 2021; Chen et al, 2020; Hammond et al, 2019; Hasel et al, 2017; He et al, 2016; Traag et al, 2019; Yao et al, 2021). We then subclustered neurons into excitatory and inhibitory subpopulations and overlaid expression of the viral transgenes.…”
Section: Resultsmentioning
confidence: 99%
“…A further elucidation of the developmental landscape of human early OPC was recently shown, using engineered knock-in hESC-reporter lines, with a tag under the endogenous, OPC-specific, PDGFRα promoter. Time-course sc RNA-sequencing of purified OPCs uncovered transcriptional heterogeneity of PDGFRα + OPCs; pseudotime analysis allowed to identify two distinct developmental trajectories for OLs vs. astrocytes differentiation from OPCs, and highlighted mTOR and cholesterol biosynthesis as key signaling pathways in the maturation of OLs from OPCs ( Chamling et al, 2021 ). Moreover, in another study, authors applied sc RNA sequencing to OL-lineage cells isolated from surgical tissues over second-trimester fetal, 2-year-old pediatric, 13-year-old adolescent, and adult donors, thereby covering advanced developmental stages including time of peak myelination.…”
Section: Unraveling Oligodendroglial Heterogeneity With Single-cell Omicsmentioning
confidence: 99%